2004
DOI: 10.1039/b407964g
|View full text |Cite
|
Sign up to set email alerts
|

Ring-closing metathesis in biphasic BMI·PF6ionic liquid/toluene medium: a powerful recyclable and environmentally friendly process

Abstract: Biphasic BMI[middle dot]PF(6)/toluene solvent is a remarkably suitable and clean medium for performing olefin metathesis with a new 2nd generation ionic liquid supported-ruthenium catalyst: high levels of recyclability and reusability combined with a high reactivity were obtained with a variety of di- or tri-substituted and/or oxygen-containing dienes, and very low residual ruthenium levels were detected (1 to 22 ppm) in the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…In order to develop a more environmentally friendly olefin metathesis process in RTILs [11], we have recently immobilized the ruthenium catalysts 8 [12] and 9 [13] in the 1-butyl-3-methylimidazolium hexafluorophosphate (BMI AE PF 6 ) 1. In a pioneering work, Buisjmann and co-workers [11a] had observed that the GrubbsÕ catalyst 2 dissolved in BMI AE PF 6 promoted the RCM of several dienes for at least three cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop a more environmentally friendly olefin metathesis process in RTILs [11], we have recently immobilized the ruthenium catalysts 8 [12] and 9 [13] in the 1-butyl-3-methylimidazolium hexafluorophosphate (BMI AE PF 6 ) 1. In a pioneering work, Buisjmann and co-workers [11a] had observed that the GrubbsÕ catalyst 2 dissolved in BMI AE PF 6 promoted the RCM of several dienes for at least three cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most commonly employed strategies to obtain supported metathesis catalysts consist of immobilizing the ruthenium alkylidene complex on to insoluble polymers, [19][20][21][22] soluble polymers, [23][24][25][26] inorganic supports, 27-29 perfluorinated 30,31 and ionic-liquid tags. [32][33][34][35] ( Figure 1). Herein we will focus on the use of soluble polymer supported Nheterocyclic carbene (NHC) Ru metathesis catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 8a, 285 ppm of Ru were found in the product; with 8b, the value was 684 ppm of Ru [43]. These results were not as low as the best systems reported so far [31][32][33][34][35] but were in the range observed for other supported Ru-complexes [36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 55%
“…Several time-consuming or cost-intensive methods were developed to reduce the metal contamination after reaction [12][13][14][15][16]. Immobilization of the Ru-complexes is a strategy to avoid the contamination from the very start as can be seen in the literature [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%